Star trek, into darkness : a novelization - Foster, Alan Dean, 1946-; Orci, Roberto; Kurtzman, Alex.; Lindelof, Damon, 1973-; Roddenberry, Gene. (New York : Gallery Books, 2013)
'The crew of the U.S.S. Enterprise--including Captain James T. Kirk, First Officer Spock, Doctor Leonard McCoy, Lieutenant Nyota Uhura, Chief Engineer Montgomery Scott, Lieutenant Hikaru Sulu, and Ensign Pavel Chekov--is called back home. But an unstoppable force of terror from within their own organization has declared all-out war on Starfleet and everything it stands for, leaving Earth in a state of crisis. Now with a personal score to settle as a result, Kirk must lead a covert manhunt to a war-zone world to capture a one-man weapon of mass destruction'--Page 4 of cover.
'Based on the motion picture screenplay by Roberto Orci, Alex Kurtzman, & Damon Lindelof; based upon Star Trek created by Gene Roddenberry.'
Keywords: Kirk, James T. -- (Fictitious character), -- 2233-2371 -- Fiction; Spock, -- Mr. -- Fiction; Human-alien encounters -- Fiction; Space warfare -- Fiction; Interstellar travel -- Fiction; Time travel -- Fiction; Star Trek fiction; Science fiction